FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU PEKERJA DALAM PENGGUNAAN APD DI SENTRA PENGASAPAN IKAN KELURAHAN BANDARHARJO KOTA SEMARANG - Fitriana Candra Dewi; Priyadi Nugraha Prabamurti (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
In 2016 the incidence of occupational accidents and diseases in Indonesia is increasing both in the formal and non-formal sectors. This is caused by the lack of awareness of workers in the use of PPE (Personal Protective Equipment) when doing work activities that provide opportunities for work accidents. In 2015 the percentage of manpower does not use PPE that suffered a work accident of 62.3%. The purpose of this study to determine the factors associated with employee behavior in the use of PPE.Type of descriptive analytic research with quantitative approach. The sample in this study using total population on all workers at Fish Fogging Center is 67 people. Data collection was done through interview using questionnaire. Data analysis used Fisher's Exact Test with significance level of 5%.The results showed that as many as 32.8% of workers already have good behavior in the use of PPE. Variables related to behavioral practices of using PPE were family support (p = 0.000), superiors support (p = 0.003) and peer support (p = 0.033). The variables unrelated to the behavior of APD usage were age (p = 0.758), education (p=1.000), knowledge (p = 1,000), attitude (p = 0.431), availability of infrastructure (p = 0.068), ease of information access (p = 0.305) Information (p = 0.175).This study concludes the importance of family support, boss support and peer support in the use of PPE. So it is advisable to health workers to increase support in the use of PPE and for the Fogging Center in order to improve the availability of infrastructure to support the behavior of the use of PPE to workers.